A multi-component composite catalytic electrode for iron-chromium flow batteries and a sol-gel preparation method thereof

CN122950504APending Publication Date: 2026-10-20ZHONGHAI ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611404745.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]为解决现有技术中存在的制备工艺复杂冗长、成本高、与铁铬电池体系兼容性差、高温热解过程可控性不足导致催化剂易烧结失活、物理浸渍负载方式导致活性组分分布不均及堵塞孔隙、以及功能设计单一无法实现多重协同催化等问题,本发明提供了一种铁铬液流电池用多组分复合催化电极及其溶胶-凝胶原位制备方法

Benefits of technology

(1)本发明通过多组分金属醇盐共水解-共缩聚溶胶-凝胶工艺,在铁铬液流电池复合催化电极制备方面取得了显著的技术进步;实施例1制备的多组分(TiO2+Bi2O3 +SnO2)复合催化碳布电极在80mA/cm2的电流密度下的初始能量效率(EE)达到86.4%,较单一TiO2对照(83.7%)提升了2.7个百分点;实施例4制备的多组分(TiO2+Bi+Sn+In四元体系)复合催化碳布电极在80mA/cm2的电流密度下的初始能量效率达到87.3%,较实施例1进一步提升约0.9%;即本发明通过多组分协同催化和原位化学锚定,在保证高初始性能的同时赋予了电极优异的长期循环稳定性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a multi-component composite catalytic electrode for iron-chromium flow batteries and its sol-gel preparation method. By designing a multi-component metal alkoxide co-hydrolysis-co-condensation sol system, and employing a one-step sol preparation and impregnation coating process combined with high-pressure gas purging and high-humidity in-situ co-gelation, a composite catalytic layer containing TiO2 and multiple components such as bismuth, tin, indium, and lead can be integrally constructed in situ on the surface of carbon cloth fibers. Through multi-component synergistic catalysis and in-situ chemical anchoring, this invention endows the electrode with excellent long-term cycling stability while ensuring high initial performance. The static water contact angle of the prepared carbon cloth fiber surface is 0°, indicating that the TiO2 framework dominates the hydrophilicity, and the introduction of multiple components does not have a negative impact on hydrophilicity. At the same time, the prepared composite catalytic layer achieves uniform, continuous, and crack-free coating on the carbon fiber surface. This provides reliable technical support for the preparation of high-performance iron-chromium flow battery electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage technology, specifically to a multi-component composite catalytic electrode for iron-chromium redox flow batteries and its sol-gel preparation method. Background Technology

[0002] With the rapid expansion of grid-connected power generation from renewable energy sources such as wind and solar, large-scale, long-duration energy storage technology has become a key support for ensuring the stable operation of the power grid. Iron-chromium redox flow batteries (ICRFBs), with their inherent advantages such as abundant electrolyte raw materials (Fe and Cr), low cost, high safety, and long cycle life, are widely recognized as one of the most commercially promising large-scale stationary energy storage technologies.

[0003] Electrodes, as the core site of electrochemical reactions, directly determine the ohmic polarization, electrochemical polarization, and mass transfer polarization of the battery. Currently, carbon-based porous materials (such as carbon felt, carbon cloth, and graphite felt) have become the mainstream choice for iron-chromium redox flow battery electrodes due to their excellent electronic conductivity, electrochemical stability over a wide potential window, and three-dimensional network structure. Among them, carbon cloth, compared to traditional thick carbon felt (thickness typically > 3 mm), has advantages such as thinner thickness (0.5–2 mm), regular weave structure, low sheet resistance, good flexibility, and suitability for compact stack design, making it particularly suitable for the assembly requirements of high-power-density stacks. Despite these structural advantages, carbon cloth still faces the following technical bottlenecks when used directly as an electrode in iron-chromium redox flow batteries: the inherent hydrophobic properties of carbon fiber surfaces result in extremely poor electrolyte wettability, and carbon cloth exhibits poor adhesion to Cr... 3+ / Cr 2+ The electrocatalytic activity of the redox couple is severely insufficient, and the hydrogen evolution side reaction is intense. Existing carbon cloth modification technology has multiple defects such as single catalytic function, uneven loading and weak binding force.

[0004] To address the aforementioned technical bottlenecks, this invention proposes an in-situ composite catalytic layer construction technology based on multi-component metal alkoxide co-hydrolysis-co-condensation sol-gel chemistry. This technology precisely controls the hydrolysis and condensation kinetics of tetrabutyl titanate (TBOT) with metal salt precursors such as bismuth, tin, indium, and lead to induce a multi-component "liquid-to-solid" in-situ co-gelation transformation on the surface of carbon cloth three-dimensional fibers. It aims to simultaneously overcome multiple challenges such as low catalytic activity of chromium reaction, severe hydrogen evolution side reactions, and weak binding force, achieving a synergistic effect of "catalysis and hydrogen suppression". Summary of the Invention

[0005] To address the problems of complex and lengthy preparation processes, high costs, poor compatibility with iron-chromium battery systems, insufficient controllability of high-temperature pyrolysis leading to catalyst sintering and deactivation, uneven distribution of active components and pore blockage caused by physical impregnation loading methods, and the inability to achieve multiple synergistic catalysis due to single functional design in existing technologies, this invention provides a multi-component composite catalytic electrode for iron-chromium flow batteries and its sol-gel in-situ preparation method. This method designs a multi-component metal alkoxide co-hydrolysis-co-condensation sol system, employs a one-step sol preparation and impregnation coating, and combines high-pressure gas purging and high-humidity in-situ co-gelation processes to integrally construct a multi-component composite catalytic layer containing TiO2 and bismuth, tin, indium, lead, etc., on the surface of carbon cloth fibers. This invention abandons the complex, multi-step, and energy-intensive process routes of existing technologies, and effectively improves the chromium content of chromium through molecular-level uniform dispersion and synergistic catalysis. 3+ / Cr 2+ The reaction kinetics were improved and the hydrogen evolution side reaction was suppressed. At the same time, the catalyst layer was firmly anchored by forming MOC chemical covalent bonds through high-temperature conversion, avoiding the problems of sintering deactivation and detachment of active components. This enabled the simple, low-cost, and controllable preparation of high-performance catalytic electrodes, solving the problems mentioned in the background technology.

[0006] To achieve the above technical effects, the following technical solution is adopted: A sol-gel preparation method for a multi-component composite catalytic electrode for iron-chromium flow batteries includes the following steps: Step S1: Pre-treat the surface of the carbon cloth using air thermal oxidation or acid oxidation processes; Step S2: Dissolve the metal salt precursor in ethylene glycol and stir for 3-5 min until completely dissolved; then add tetrabutyl titanate to the above solution and continue stirring for 5-8 min until a mixed solution is formed; finally, add glacial acetic acid and deionized water dropwise to the mixed solution; after the addition is complete, seal the system and continue stirring for 20-40 min to obtain a composite sol liquid, thus preparing a multi-component metal alkoxide composite sol; the metal salt precursor is selected from one or more of the following metal salts: bismuth salt, tin salt, indium salt, and lead salt; Step S3: Immerse the carbon cloth pretreated in step S1 completely in the multi-component metal alkoxide composite sol prepared in step S2, let it stand for 3-5 minutes, take it out and hang it vertically, and use N2 or inert gas spray gun to blow it. Step S4: Transfer the carbon cloth after airflow purging to a sealed constant temperature and humidity chamber or glass desiccator with deionized water at the bottom, at a temperature of 20-30℃ and a humidity of 80%-95%, and let it stand for 18-30 hours. Step S5: Take out the carbon cloth that has been aged and coated with a multi-component composite wet gel layer, lay it flat on a clean polytetrafluoroethylene drying plate, and put it in a constant temperature drying oven at 70-90℃ for 1-3 hours. Step S6: Place the dried carbon cloth into the constant temperature zone of the tubular resistance furnace, seal it, and introduce N2 or Ar gas to remove air; raise the furnace temperature from room temperature to 400-500℃ at a heating rate of 3-10℃ / min, and keep it at this temperature for 2-3 hours. After the holding period, cool it to room temperature with the furnace under the protection of N2 or Ar atmosphere at a cooling rate of 1-5℃ / min to obtain a multi-component composite catalytic carbon cloth electrode. Furthermore, in step S1, the carbon cloth is a polyacrylonitrile-based carbon cloth with a thickness of 0.5–2.0 mm and a unit area mass of 100–500 g / m². 2 .

[0007] Furthermore, in step S1, the air thermal oxidation pretreatment process for the carbon cloth surface is as follows: the carbon cloth is placed in a muffle furnace with a programmable temperature control, heated to 350-450°C at a heating rate of 3-8°C / min in an air atmosphere, and then kept at a constant temperature for 1-3 hours before being cooled with the furnace. Furthermore, in step S1, the acid oxidation pretreatment process for the carbon cloth surface is as follows: the carbon cloth is placed in concentrated nitric acid with a concentration of 65% to 68%, refluxed and heated to boiling for 0.5 to 2 hours, then repeatedly rinsed with deionized water until the pH of the supernatant is neutral, and finally placed in an 80°C vacuum drying oven to dry for later use. Furthermore, in step S2, the molar ratio of each component in the metal alkoxide composite sol is: tetrabutyl titanate: ethylene glycol: glacial acetic acid: deionized water: metal salt precursor = 1 : (10-40) : (1-5) : (0.5-2) : (0.01-0.3); Furthermore, in step S2, the bismuth salt is selected from one or two of bismuth nitrate or bismuth chloride, the tin salt is selected from one or two of stannous chloride or stannous tetrachloride, the indium salt is selected from one or two of indium nitrate or indium chloride, and the lead salt is selected from one or two of lead acetate or lead nitrate. Furthermore, in step S3, the gas spray gun is an industrial nitrogen gun with a purity of ≥99.99% and a gas pressure of 0.4~0.8 MPa; the purging method is: purging both sides of the carbon cloth perpendicular to the cloth surface direction, with a purging time of 5~15 s per side, until no droplets continuously drip.

[0008] On the other hand, the present invention provides a multi-component composite catalytic carbon cloth electrode prepared by the above preparation method.

[0009] On the other hand, the present invention also provides a method for applying the above-mentioned multi-component composite catalytic carbon cloth electrode in the assembly of the negative electrode of the iron-chromium flow battery, which assembles the multi-component composite catalytic carbon cloth electrode with Nafion series proton exchange membrane, positive electrode and iron-chromium electrolyte into a single iron-chromium flow battery cell. Furthermore, the iron-chromium electrolyte includes FeCl2, CrCl3, HCl, and deionized water.

[0010] The beneficial effects of this invention are as follows: (1) This invention has achieved significant technological progress in the preparation of composite catalytic electrodes for iron-chromium flow batteries through a multi-component metal alkoxide co-hydrolysis-co-condensation sol-gel process; the multi-component (TiO2+Bi2O3+SnO2) composite catalytic carbon cloth electrode prepared in Example 1 achieves a speed of 80 mA / cm 2 The initial energy efficiency (EE) at the current density reached 86.4%, which was 2.7 percentage points higher than the single TiO2 control (83.7%). The multi-component (TiO2+Bi+Sn+In quaternary system) composite catalytic carbon cloth electrode prepared in Example 4 achieved an efficiency of 80 mA / cm². 2 The initial energy efficiency at the current density reached 87.3%, which is about 0.9% higher than that of Example 1; that is, the present invention endows the electrode with excellent long-term cycling stability while ensuring high initial performance through multi-component synergistic catalysis and in-situ chemical anchoring. (2) In terms of physical properties, the composite catalyst layer prepared by the present invention achieves uniform, continuous and crack-free coating on the carbon fiber surface; the functional metal oxides are uniformly distributed in the TiO2 framework in the form of nanoclusters or atomic-level dispersion; the hydrophilicity test shows that the static water contact angle of Example 1 is 0°, which is much lower than that of the original carbon cloth (128.5°), indicating that the TiO2 framework dominates the hydrophilicity and the introduction of multiple components does not have a negative impact on the hydrophilicity. (3) In terms of environmental and safety benefits, all processes of this invention are completed under normal pressure, without the need for high-pressure equipment, and the operating temperature does not exceed 500℃, thus avoiding the safety risks caused by high temperature and high pressure. Compared with the high-temperature pyrolysis steps in the prior art that require inert atmosphere protection, the heat treatment process of this invention can be completed under normal pressure N2 or Ar atmosphere, with low gas consumption. The organic solvents such as ethylene glycol and glacial acetic acid used in the sol preparation process can be recycled and reused through distillation, resulting in high chemical utilization and low waste emissions, which meets the requirements of green chemistry and clean production. (4) The present invention has made significant technological progress in terms of simplifying the preparation process, controlling material costs, improving electrochemical performance, long-term cycle stability, catalyst layer bonding strength, pore structure protection and environmental safety. It effectively solves the defects in the background technology, such as complex and lengthy process, poor system adaptability, uncontrollable high-temperature process, uneven distribution of active components and single functional design, and provides reliable technical support for the preparation of high-performance iron-chromium redox flow battery electrodes. Attached Figure Description

[0011] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. The drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0012] Figure 1 The image shows a scanning electron microscope (SEM) image of the multi-component composite catalytic carbon cloth electrode prepared in Example 1 of this invention. Figure 2 Photograph of the static water contact angle test of the carbon cloth electrode of Comparative Example 1 (blank control) of the present invention; Figure 3 This is a static water contact angle test photograph of the multi-component composite catalytic carbon cloth electrode prepared in Example 1 of the present invention; Figure 4 This is a static water contact angle test photograph of the binary composite catalytic carbon cloth electrode prepared in Example 2 of the present invention; Figure 5 The single cell of the iron-chromium flow battery assembled with the multi-component composite catalytic carbon cloth electrode prepared in Example 1 of this invention operates at 80 mA / cm². 2 Data on coulombic efficiency, voltage efficiency, and energy efficiency under charge-discharge cycles at current density. Detailed Implementation

[0013] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0014] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0015] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments of the present invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, and / or combinations thereof.

[0016] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the art; unless otherwise specified, the experimental methods and techniques used are conventional methods and techniques in the art.

[0017] The technical solutions provided by the present invention will be described below with reference to the embodiments. The scope of protection of the present invention is not limited by the following embodiments.

[0018] Example 1 (TiO2+Bi+Sn ternary composite system) The carbon cloth selected is polyacrylonitrile-based carbon cloth with a thickness of 0.8 mm and a unit area mass of 300 g / m². 2. First, the carbon cloth was pretreated by cutting it into squares with an effective area of ​​2 cm × 5 cm. These squares were then placed in a programmable muffle furnace and heated to 400°C at a rate of 5°C / min under air atmosphere, and held for 2 hours. After removal and natural cooling, the carbon cloth was ultrasonically cleaned three times in deionized water and dried in an 80°C oven for 12 hours. Next, a multi-component composite sol was prepared. In a glove box with a relative humidity of <30%, 0.097 g (approximately 0.2 mmol) of bismuth nitrate (Bi(NO3)3·5H2O) and 0.045 g (approximately 0.2 mmol) of stannous chloride (SnCl2·2H2O) were dissolved in 20 mL (approximately 340 mmol) of ethylene glycol and magnetically stirred for 5 minutes until completely dissolved. Then, 3.4 g (approximately 10 mmol) of tetrabutyl titanate (TBOT) was added, and stirring continued for 5 minutes. Finally, 1.2 g (approximately 20 mmol) of glacial acetic acid and 0.18 g of bismuth subnitrate were slowly added dropwise. Add mL (approximately 10 mmol) of deionized water. After the addition is complete, seal the beaker and continue stirring for 30 minutes to form a clear, transparent, pale yellow composite sol. The molar ratio of TBOT: EG: HAC: H2O: Bi: Sn in this sol is 1: 34:2: 1: 0.02: 0.02. Then, perform impregnation and high-pressure air purging. Completely immerse the pretreated carbon cloth in the newly prepared composite sol and let it stand for 5 minutes. After removal, hang it vertically and immediately use an industrial nitrogen gun (pressure set to 0.6 MPa) to sweep the front side horizontally for 10 seconds from approximately 10 cm above the cloth surface. Turn it over and sweep the back side for 10 seconds until no more droplets continuously drip. Subsequently, perform high-humidity in-situ co-aging. Place the purged carbon cloth at the bottom in a container filled with deionized water (liquid level 2...). The carbon cloth was sealed on a porous ceramic plate inside a large glass desiccator (cm) and the humidity was controlled at 92% and the temperature at 25℃. It was then left to stand for 24 hours to age. After aging, it was dried at normal pressure and constant temperature. The carbon cloth was then taken out and laid flat on a PTFE plate and placed in an 80℃ constant temperature forced-air drying oven for 2 hours. Finally, high-temperature crystallization and multiphase anchoring were carried out. The dried carbon cloth was placed in a tubular furnace quartz tube and high-purity N2 or Ar gas was introduced at a flow rate of 100 mL / min. The temperature was increased from room temperature to 450℃ at a flow rate of 5℃ / min and kept at a constant temperature for 2 hours. After the holding time, the flow rate of N2 or Ar gas was maintained and the temperature was naturally reduced to room temperature, thus forming a multi-component (TiO2+Bi2O3+SnO2) composite catalytic carbon cloth electrode.

[0019] Performance test results: such as Figure 1 As shown, scanning electron microscopy (SEM) revealed that the surface of the carbon cloth fibers was covered by a dense and uniform layer of nanoparticles with a particle size distribution of 10–100 nm. (See [link to SEM document]). Figure 1 . Figure 3 The image shows a static water contact angle test of the multi-component composite catalytic carbon cloth electrode prepared in Example 1, where the static water contact angle is 0°. Figure 5The single cell of the iron-chromium flow battery assembled with the multi-component composite catalytic carbon cloth electrode prepared in Example 1 operates at 80 mA / cm². 2 Data on coulombic efficiency, voltage efficiency, and energy efficiency during charge-discharge cycles at current density of 80 mA / cm². 2 At the current density, the initial energy efficiency of a single cell is 86.4%.

[0020] Example 2 (TiO2+In binary composite system) Preparation method: The difference between this example and Example 1 is that in the sol preparation stage, 0.06 g (approximately 0.2 mmol) of indium nitrate (In(NO3)3·xH2O) is added as a functional metal salt precursor, and bismuth nitrate and stannous chloride are not added. That is, the molar ratio of TBOT:EG:HAC:H2O:In is 1:34:2:1:0.02. The remaining steps and parameters are exactly the same as in Example 1.

[0021] Performance test results: The surface of the electrode fiber is covered with a uniform nanoparticle layer with a particle size of 10–80 nm; Figure 4 This is a photograph of the static water contact angle of the binary composite catalytic carbon cloth electrode prepared in Example 2 of this invention. The static water contact angle is 0°. (At 80 mA / cm²) 2 At the current density, the initial energy efficiency of a single cell is 85.0%.

[0022] Example 3 (TiO2+Pb binary composite system) Preparation method: The difference between this example and Example 1 is that 0.0556 g (approximately 0.2 mmol) of lead chloride (PbCl2) was added as a functional metal salt precursor during the sol preparation stage, and bismuth nitrate and stannous chloride were not added. That is, the molar ratio of TBOT:EG:HAC:H2O:Pb was 1:34:2:1:0.02. The remaining steps and parameters were exactly the same as in Example 1.

[0023] Performance test results: The electrode fiber surface is covered with a uniform nanoparticle layer with a particle size of 10–150 nm; the static water contact angle is 0°; at 80 mA / cm 2 At the current density, the initial energy efficiency of a single cell is 85.8%.

[0024] Example 4 (TiO2+Bi+Sn+In quaternary composite system) Preparation method: The difference between this example and Example 1 is that 0.097 g (0.2 mmol) of bismuth nitrate, 0.045 g (0.2 mmol) of stannous chloride, and 0.06 g (0.2 mmol) of indium nitrate were added simultaneously during the sol preparation stage as functional metal salt precursors, i.e., the molar ratio of TBOT:EG:HAC:H2O:Bi:Sn:In was 1:34:2:1:0.02:0.02:0.02. The remaining steps and parameters were exactly the same as in Example 1.

[0025] Performance test results: SEM observation showed that the electrode fiber surface was covered with a uniform layer of nanoparticles with a particle size of 5–150 nm; the static water contact angle was 0°; and the performance at 80 mA / cm² was satisfactory. 2 At the current density, the initial energy efficiency of the single cell reached 87.3%, which is about 0.9% higher than that of Example 1 (86.4%). The overall performance of the quaternary system is significantly better than that of the ternary and binary systems, which fully demonstrates the synergistic catalytic effect of the three components Bi, Sn and In on the TiO2 framework.

[0026] Comparative Example 1 (Blank Control) Commercial raw polyacrylonitrile-based carbon cloth without any surface treatment was selected, and charge-discharge tests were performed directly under the same electrolyte and battery assembly conditions as in Example 1, without any catalyst layer loading. Figure 2 A photograph of the static water contact angle of the carbon cloth electrode prepared for Comparative Example 1, showing a static water contact angle of 128.5°; at 80 mA / cm²... 2 The initial energy efficiency at current density is only 83.9%.

[0027] Comparative Example 2 (Single TiO2 control) Following the same steps as in Example 1, but without adding any functional metal salt precursors during the sol-gel preparation stage (i.e., only TBOT: EG: HAC: H2O = 1: 34: 2: 1), a single TiO2 / carbon cloth composite electrode was prepared. Its static water contact angle was 0° at 80 mA / cm². 2 The initial energy efficiency at the current density is 84.1%, and this comparative example demonstrates the necessity of introducing multiple components.

[0028] In summary, this invention provides a multi-component composite catalytic electrode for iron-chromium flow batteries and its sol-gel in-situ preparation method. This method, through the design of a multi-component metal alkoxide co-hydrolysis-co-condensation sol system, employs a one-step sol preparation and impregnation coating process, combined with high-pressure gas purging and high-humidity in-situ co-gelation, to integrally construct a multi-component composite catalytic layer containing TiO2 and bismuth, tin, indium, and lead on the surface of carbon fiber. Example 1 (TiO2+Bi+Sn ternary system) achieved an initial energy efficiency (EE) of 86.4%, a 2.7% improvement over the single TiO2 control (84.1%). Example 4 (TiO2+Bi+Sn+In quaternary system) achieved an initial energy efficiency of 87.3%, a further improvement of approximately 1% over Example 1. This invention, through multi-component synergistic catalysis and in-situ chemical anchoring, endows the electrode with excellent long-term cycling stability while ensuring high initial performance. The composite catalyst layer prepared by this invention achieves uniform and continuous coating on the carbon fiber surface. Functional metal oxides are uniformly distributed in the TiO2 framework in a nano-cluster or atomic-level dispersion state. Hydrophilicity tests show that the static water contact angle of the carbon cloth fiber surface prepared in Examples 1-4 is 0°, which is significantly lower than the static water contact angle (128.5°) of the original carbon cloth surface, indicating that the TiO2 framework dominates the hydrophilicity, and the introduction of multiple components does not have a negative impact on hydrophilicity. This invention abandons the complex process route of existing technologies with multiple steps and high energy consumption, and effectively improves the Cr content by uniformly dispersing and synergistically catalyzing each component at the molecular level. 3+ / Cr 2+ The reaction kinetics are optimized and the hydrogen evolution side reaction is selectively suppressed. At the same time, the catalyst layer is firmly anchored by forming MOC chemical covalent bonds through high-temperature conversion, avoiding the problems of sintering deactivation and detachment of active components. This enables the simple, low-cost and controllable preparation of high-performance catalytic electrodes.

[0029] Therefore, those skilled in the art will recognize that although embodiments of the present invention have been shown and described in detail herein, many other variations or modifications conforming to the principles of the present invention can be directly determined or derived from the disclosure of the present invention without departing from the spirit and scope of the invention. Therefore, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.

Claims

1. A method for preparing a sol-gel of a multi-component composite catalytic electrode for an iron-chromium flow battery, characterized in that, Includes the following steps: Step S1: Pre-treat the surface of the carbon cloth using air thermal oxidation or acid oxidation processes; Step S2: Dissolve the metal salt precursor in ethylene glycol and stir for 3-5 min until completely dissolved; then add tetrabutyl titanate to the above solution and continue stirring for 5-8 min until a mixed solution is formed; finally, add glacial acetic acid and deionized water dropwise to the mixed solution; after the addition is complete, seal the system and continue stirring for 20-40 min to obtain a composite sol liquid, thus preparing a multi-component metal alkoxide composite sol; the metal salt precursor is selected from one or more of the following metal salts: bismuth salt, tin salt, indium salt, and lead salt; Step S3: Immerse the carbon cloth pretreated in step S1 completely in the multi-component metal alkoxide composite sol prepared in step S2, let it stand for 3-5 minutes, take it out and hang it vertically, and use N2 or inert gas spray gun to blow it. Step S4: Transfer the carbon cloth after airflow purging to a sealed constant temperature and humidity chamber or glass desiccator with deionized water at the bottom, at a temperature of 20-30℃ and a humidity of 80%-95%, and let it stand for 18-30 hours. Step S5: Take out the carbon cloth that has been aged and coated with a multi-component composite wet gel layer, lay it flat on a clean polytetrafluoroethylene drying plate, and put it in a constant temperature drying oven at 70-90℃ for 1-3 hours. Step S6: Place the dried carbon cloth into the constant temperature zone of the tubular resistance furnace, seal it, and introduce protective gas to remove air; raise the furnace temperature from room temperature to 400-500℃ at a heating rate of 3-10℃ / min, and keep it at this temperature for 2-3 hours. After the holding period, cool it to room temperature with the furnace under the protection of N2 or an inert atmosphere at a cooling rate of 1-5℃ / min to obtain a multi-component composite catalytic carbon cloth electrode.

2. The method for preparing a sol-gel of a multi-component composite catalytic electrode for an iron-chromium flow battery as described in claim 1, characterized in that, In step S1, the carbon cloth is a polyacrylonitrile-based carbon cloth with a thickness of 0.5–2.0 mm and a unit area mass of 100–500 g / m². 2 .

3. A method for preparing a sol-gel of a multi-component composite catalytic electrode for an iron-chromium flow battery as described in any one of claims 1 to 2, characterized in that, In step S1, the air thermal oxidation pretreatment process for the carbon cloth surface is as follows: the carbon cloth is placed in a muffle furnace with a programmable temperature control, heated to 350-450°C at a heating rate of 3-8°C / min in an air atmosphere, and then kept at a constant temperature for 1-3 hours before being cooled with the furnace.

4. A method for preparing a sol-gel of a multi-component composite catalytic electrode for an iron-chromium flow battery as described in any one of claims 1 to 2, characterized in that, In step S1, the acid oxidation pretreatment process for the carbon cloth surface is as follows: the carbon cloth is placed in concentrated nitric acid with a concentration of 65% to 68%, refluxed and heated to boiling for 0.5 to 2 hours, then repeatedly rinsed with deionized water until the pH of the supernatant is neutral, and finally placed in an 80°C vacuum drying oven to dry for later use.

5. The method for preparing a sol-gel of a multi-component composite catalytic electrode for an iron-chromium flow battery as described in claim 1, characterized in that, In step S2, the molar ratio of each component in the metal alkoxide composite sol is: tetrabutyl titanate: ethylene glycol: glacial acetic acid: deionized water: metal salt precursor = 1 : (10~40) : (1~5) : (0.5~2) : (0.01~0.3).

6. The method for preparing a sol-gel of a multi-component composite catalytic electrode for an iron-chromium flow battery as described in claim 1, characterized in that, In step S2, the bismuth salt is selected from one or two of bismuth nitrate or bismuth chloride, the tin salt is selected from one or two of stannous chloride or stannous tetrachloride, the indium salt is selected from one or two of indium nitrate or indium chloride, and the lead salt is selected from one or two of lead acetate or lead nitrate.

7. The method for preparing a sol-gel of a multi-component composite catalytic electrode for an iron-chromium flow battery as described in claim 1, characterized in that, In step S3, the gas spray gun is an industrial nitrogen gun with a purity of ≥99.99% and a gas pressure of 0.4~0.8 MPa; the purging method is to blow the carbon cloth on both sides perpendicular to the cloth surface, and the purging time is 5~15 s per side until no droplets drip continuously.

8. The multi-component composite catalytic carbon cloth electrode prepared by the preparation method according to any one of claims 1 to 7.

9. The method of applying the multi-component composite catalytic carbon cloth electrode as described in claim 8 in the assembly of the negative electrode of an iron-chromium flow battery, characterized in that, A multi-component composite catalytic carbon cloth electrode was assembled with a Nafion series proton exchange membrane, a positive electrode, and an iron-chromium electrolyte to form an iron-chromium flow battery.

10. The application method as described in claim 9, characterized in that, The iron-chromium electrolyte contains FeCl2, CrCl3, HCl, and deionized water.